Examining the Impacts of Human Capital Flight on Economic Growth: A Case Study of Pakistan - Younas, Muhammad Zeeshan; Ahmad, Ghazala (Review of Knowledge Economy, 2020)
Human capital is one of the key drivers of economic development and sustainable competitive advantage in the global market. Human capital flight or Brain drain can lead to a permanent impact on the growth process of the country of emigration. Like numerous other developing countries, Pakistan has also been experiencing both the negative and positive consequences of human capital flight. To examine these impacts of international movements on Pakistan economy we retrieved data from different sources. The fundamental objective is to examine the consequences of international migration and its associations with poverty, economic growth, and human development. To keep this in mind, we employed the ARDL approach on three different models for the period of 1975 to 2017. District wise analysis of all provinces states that the international migration is playing a key role in the reduction of poverty level except in KPK. In addition, empirical evidence describes that international migration is positively associated with economic growth and human development while negatively associated with poverty level. The study is concluding that there are enormous potential benefits exists in international migration process because it boosts the economic growth of Pakistan via personal remittances inflow. Likewise, it smoothes out the consumption pattern of ordinary households due to the direct transfer of remittances to them. This monograph is also suggesting some useful policy recommendations for instance, if we export our manpower to highly developed countries then reverse brain drain will encourage the innovation practices along with improvement in economic growth.